2018
DOI: 10.1016/j.ygyno.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-integrated risk profile to determine adjuvant radiotherapy in endometrial cancer: Evaluation of the pilot phase of the PORTEC-4a trial

Abstract: The PORTEC-4a trial design was proven feasible with a satisfactory patient acceptance rate and an optimized workflow of the determination of the molecular-integrated risk profile. PORTEC-4a is the first randomized trial to investigate use of a molecular-integrated risk profile to determine adjuvant treatment in EC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 28 publications
1
93
0
1
Order By: Relevance
“…Apart from cervical cancer, major indications for brachytherapy are endometrial, prostate, and breast cancer (Table ). For these tumor sites, the level of evidence for brachytherapy has come from randomized controlled studies focusing not only on local control but also including OS and QOL analysis (Table ) …”
Section: Brachytherapy In the Global Oncological Landscapementioning
confidence: 99%
See 2 more Smart Citations
“…Apart from cervical cancer, major indications for brachytherapy are endometrial, prostate, and breast cancer (Table ). For these tumor sites, the level of evidence for brachytherapy has come from randomized controlled studies focusing not only on local control but also including OS and QOL analysis (Table ) …”
Section: Brachytherapy In the Global Oncological Landscapementioning
confidence: 99%
“…Therefore, the modern management of endometrial cancers is tailored to each specific situation and is part of a multimodal approach aimed at decreasing morbidity without jeopardizing the probability of survival. The phase 3 Post‐Operative Radiation Therapy in Endometrial Carcinoma 4 (PORTEC‐4) study evaluates the possibility of guiding adjuvant treatments in high‐intermediate risk endometrial cancer based on a molecular‐integrated risk profile . Thus, regarding endometrial cancer treatment, a close collaboration is required with gynecological oncologists to move from a standard approach to risk‐adapted strategies.…”
Section: Brachytherapy In the Global Oncological Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…For women with tumors harboring a POLE mutation, 10-year CSS was 100%, in contrast to 96.2% for no specific molecular profile, 84.8% for MSI and 62.3% for p53-mutant tumors (p < 0.001) [32]. This knowledge is being tested in the on-going PORTEC IVA trial [45] where molecular testing is stratifying patients to observation, VCB, or WPRT.…”
Section: Adjuvant Management Of Early Stage Endometrial Cancermentioning
confidence: 99%
“…2D and Figure S2E) but had much worse prognosis than wide types ( Fig. 2F) (5,31). Multivariable Cox models further demonstrated that CTNNB1 mutation was an unfavorable prognostic factor independent of CIN signatures in OB and EBRT subgroups ( Table 2 and Table 3).…”
Section: Relationships Between Cin and Prognostic Factors Of Moleculamentioning
confidence: 82%